Enhancement of Transmission System Security with Archimedes Optimization Algorithm - Doğan, Erdi; Yörükeren, Nuran (Turkish Journal of Electrical Power and Energy Systems, 2022)
The reliability of the transmission system is crucial in terms of both economic and social welfare. On one hand, the transmission lines getting overloaded because of a single outage situation may give rise to even a blackout. On the other hand, the excessive short-circuit current might cause distortion of valuable system devices. Therefore, the static security of the transmission system should be provided so as to protect consumers and system components. The bus splitting optimization (BSO) is a tool that maintains system security by distributing transmission feeders to the suitable busbars. The BSO is a non-convex, combinatorial, and binary problem due to AC power flow equations, short-circuit calculations, and the nature of the representation of the feeder position. Hence, the novel Archimedes optimization algorithm (AOA) is utilized in order to solve the BSO problem instead of the deterministic approaches in this study. Analyses we implemented show that the AOA algorithm has the efficacy and robustness to solve the BSO problem in the Istanbul Anatolian Region of the Turkish Electricity Transmission System and to enhance the power system security. Cite this article as: E. Doğan, N. Yörükeren. Enhancement of transmission system security with archimedes optimization algorithm, Turk J Electr Power Energy Syst, 2022; 2(2), 115-123.